150 Million year history of North China Craton disruption preserved in Mesozoic sediments of the Ordos basin. Issue 11 (17th August 2016) - Li, Zhen-Hong; Xi, Sheng-Li; Feng, Sheng-Bin; Liu, Xin-She
ABSTRACT: The Ordos Basin, situated in the western part of the North China Craton, preserves the 150-million-year history of North China Craton disruption. Those sedimentary sources from Late Triassic to early Middle Jurassic are controlled by the southern Qinling orogenic belt and northern Yinshan orogenic belt. The Middle and Late Jurassic deposits are received from south, north, east, and west of the Ordos Basin. The Cretaceous deposits are composed of aeolian deposits, probably derived from the plateau to the east. The Ordos Basin records four stages of volcanism in the Mesozoic–Late Triassic (230–220 Ma), Early Jurassic (176 Ma), Middle Jurassic (161 Ma), and Early Cretaceous (132 Ma). Late Triassic and Early Jurassic tuff develop in the southern part of the Ordos Basin, Middle Jurassic in the northeastern part, while Early Cretaceous volcanic rocks have a banding distribution along the eastern part. Mesozoic tectonic evolution can be divided into five stages according to sedimentary and volcanic records: Late Triassic extension in a N–S direction (230–220 Ma), Late Triassic compression in a N–S direction (220–210 Ma), Late Triassic–Early Jurassic–Middle Jurassic extension in a N–S direction (210–168 Ma), Late Jurassic–Early Cretaceous compression in both N–S and E–W directions (168–136 Ma), and Early Cretaceous extension in a NE–SW direction (136–132 Ma).